2021
DOI: 10.37105/iboa.124
|View full text |Cite
|
Sign up to set email alerts
|

Enviromental factors as the elements determing the development of floating homes

Abstract: The popularity of Floating Homes in Western Europe and North America is noticeable. The interest in these facilities in Poland is also constantly growing. The popularity of Floating Homes is due to climate change, rising land prices and population density in city centers. However, environmental factors play a significant role in their development. The publication presents the results of research on the impact of environmental factors on the development of Floating Homes in Poland. As part of the research, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The width of the funnel increases with greater degrees of uncertainty, and longer forecast periods [34,35]. Our procedure for conducting studies connected with the development of FHs, following the methodologies of the works [35][36][37][38], is composed of four stages:…”
Section: Methodology Of Conducting Studies Using Ssssmentioning
confidence: 99%
See 2 more Smart Citations
“…The width of the funnel increases with greater degrees of uncertainty, and longer forecast periods [34,35]. Our procedure for conducting studies connected with the development of FHs, following the methodologies of the works [35][36][37][38], is composed of four stages:…”
Section: Methodology Of Conducting Studies Using Ssssmentioning
confidence: 99%
“…an upward trend in the process in the future: the potential negative or positive impact of the trend, and the likelihood of its occurrence; -a stabilization tendency in the process in the future: the potential negative or positive impact of the trend, and the likelihood of its occurrence; or a downward trend in the process in the future: the potential negative or positive impact of the trend, and the likelihood of its occurrence. Our procedure for conducting studies connected with the development of FHs, following the methodologies of the works [35][36][37][38], is composed of four stages:…”
Section: Second Stagementioning
confidence: 99%
See 1 more Smart Citation
“…In the presented research, individual factors were identified at an earlier stage, when developing scenarios for the future development of FHs in Poland using the SSSs method. The research was presented in publications: [21,[23][24]. The determinants were selected based on a literature review, survey, interview and own observations.…”
Section: Input Data For Developing the Strategymentioning
confidence: 99%
“…Development strategies should include solutions to formal and legal [1][2][3][4][5][6][7][8][9], technical [5,[10][11][12][13][14], economic [1-3, 5, 7-8], environmental [15][16][17][18][19][20][21][22][23][24], demographic and socio-cultural [2,[25][26] issues.…”
Section: Introductionmentioning
confidence: 99%